the Exploring Beginner Free diver’s Experience of Benefit Recreational Freediving Activity - Muhamad Nanang Solikhin; Fauzi fauzi; Sulistiyono Sulistiyono; Caly Setiawan; Lailla Affianti Fauzi (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The purpose of this article is to explore the experience of an Indonesian beginner free diver perspective while practicing programmed recreational freediving. This freediving recreational theme tries to be built from the experience of a beginner free diver who obtains mental and physical health benefits from relaxation and other physical aspects through diving. This is to support the program for further development of freediving recreation as a choice of physical activity in free time. A qualitative methodology has been used twenty-six freedivers aged between 18 and 43 years were recruited to participate in the study. In-depth interviews were specifically designed to collect data about the forms of experience, learning, motivation, positive mental involvement through recreational freediving activities carried out. Data were collected with anecdotal notes through interviews and submitted to inductive content analysis in the ATLAS.ti 9 program. Physical theoretical literacy analysis was used to address the empirical data analysis. The results showed patterns in the data, including information gathering physical exercises, mental training, engagement as a learning journey, and experience and withdrawal from recreational freediving performed. It is concluded that this type of recreational freediving exercise provides a form of physical activity that provides mental and physical benefits for novice freediving.